BAZI DOĞRUSAL OLMAYAN KISMİ DİFERENSİYEL DENKLEMLERİN SONLU FARKLAR METODU İLE SAYISAL ÇÖZÜMÜ - PARTAL, TUĞÇEM (Fırat Üniveristesi, 2011)
Bu çalışma üç bölümden oluşmaktadır.Birinci bölümde, diferansiyel denklemlerle ilgili temel tanımlara yer verilmiştir.İkinci bölümde Sonlu fark metodu, Adomian ayrışım metodu ve Homotopi Pertürbasyon metotlarının genel yapıları anlatılmıştır.Üçüncü bölüm ise tezimizin orijinal kısmını oluşturmaktadır ve iki kısımdır. Birinci kısımda KdV denklemine sırasıyla SFM, ADM ve HPM uygulanarak denklemin sayısal çözümleri incelenmiştir. İkinci kısımda ise, Burgers denklemine SFM, ADM ve HPM uygulanarak denklemin sayısal çözümleri incelenmiştir.Anahtar Kelimeler: KdV denklemi, Burgers denklemi, Sonlu Fark Metodu (SFM),Adomian Ayrışım Metodu (ADM), Homotopi PertürbasyonMetodu (HPM), Crank Nicolson, Adomian Polinomları,Sonlu Fark Yaklaşımı.

This thesis consists of three chapters.In the first chapter, provides fundamental definitions related to differential equations.In the second chapter, we give general structures of Finite Difference Method, Adomian Decomposition Method and Homotopy Perturbation Method.The third chapter is the our major contribution and it has two section. In the first section of third chapter, numerical solitions of the KdV equation were investigated by applying Finite Difference Method, ADM and HPM methods respectively to the KdV equation. In the second section of third chapter, numerical solitions of the Burgers equation were investigated by applying Finite Difference Method, ADM and HPM methods respectively to the Burgers equation.Key Words: KdV equation, Burgers equation, Finite Difference Method (SFM),Adomian Decomposition Method (ADM), Homotopy PerturbationMethod (HPM), Crank Nicolson, Adomian Polinomials, Finite Dif-ference Approximation.
Solutions of some non-linear partial differential equations with finite difference method
Keywords: Matematik